New diatom species Navicula davidovichii from Vietnam (Southeast Asia) - Kulikovskiy, Maxim; Chudaev, Dmitry; Glushchenko, Anton; Kuznetsova, Irina; Kociolek, John Patrick (Phytotaxa, 2020)
We present light and scanning electron microscopical observations on one new species of Navicula Bory sensu stricto from Vietnam. The new species, Navicula davidovichii Chudaev, Glushchenko, Kulikovskiy & Kociolek sp. nov., possesses all typical morphological features for the genus, including uniseriate striae covered by internal convex hymenes, median raphe with accessory rib at the internal surface, and hooked external distal raphe ends. Navicula davidovichii sp. nov., is distinguished from others in the genus on the basis valve outline, shape of the apices, as well as striae and areolar densities. The very interesting shape of the valve, with widely rounded capitate apices, is more typical for species in the genus Pinnularia than in Navicula. Morphologically similar species are almost unknown, except possibly Navicula reinhardtii (Grunow) Grunow. Comparison with the above-mentioned species is given.